Double-blind, Randomized Evaluation of Clinical Efficacy and Tolerability of an Apple Pectin-Chamomile Extract in Children with Unspecific Diarrhea - Becker, Brigitta; Kuhn, Ulrike; Hardewig-Budny, Bettina (Arzneimittelforschung, 2006)
Background: Acute diarrhea is one of the most common childhood diseases. The main aim of therapy is oral rehydration, mostly using a glucose-electrolyte solution. Results from a previous study (DIALOG I) investigating adjuvant treatment with a medicinal preparation containing an apple pectin-chamomile extract (Diarrhoesan®) indicated a significantly reduced duration of diarrhea in children.Objectives: The objective of the present clinical placebo-controlled, double-blind study (DIALOG II) was to assess the clinical efficacy and tolerability of the apple pectin-chamomile extract on a larger number of patients.Methods: The investigation was designed as a multicenter, randomized, double-blind, placebo-controlled parallel study enrolling 255 patients presenting with acute diarrhea. Patients were aged between 6 months and 6 years and treated on an outpatient basis with either an apple pectin-chamomile preparation or placebo. As a basic medication, each child received a glucose-electrolyte solution on the first day of treatment.Results: The primary outcome (primary efficacy parameter) included a combined analysis of stool frequency, stool consistency and duration of diarrhea.The statistical analysis revealed a superior efficacy of the tested preparation over placebo with a significantly reduced stool frequency in the treatment group compared to the control group. The results were corroborated by efficacy assessment performed by investigators and patients. Treatment was well tolerated, with an incidence of adverse effects similar to placebo.Conclusion: These findings support the concept of a beneficial influence of the investigated vegetable extract in shortening the course of the disease and relieving associated symptoms.
Keywords: Diarrhea, children; Diarrhoesan®, children, efficacy, tolerability; Gastroenteritis; Pectin-chamomile extract